Tax Management on Income Tax article 21 at PT Cahaya Abadi Lestari - Anita Ludia Vivian Wauran; Milleano Gilbert Ludowyk Wuwung; Treesje Amelia Clara Langi (Future Science, 2023)
Tax is a source of state revenue for the implementation of government and development activities as well as a stimulus for economic activity. Revenue from the tax sector greatly supports the implementation of development in various sectors as a form of government service to the community. Income tax is a type of tax collected by the government based on law number 36 of 2008. Income tax has great potential for the government in the taxation sector, income tax (PPh) includes general income tax, PPh 21, PPh 22, PPh 23, PPh 24, PPh 25, PPh 26. The purpose of this study is to find out whether the calculation and reporting of income tax at PT.Cahaya Abadi Lestari is in accordance with law No.36 of 2008. Research Methods, The method used in this research is descriptive quantitative. From the results of this study it is known that with the existence of tax management on PPH 21, the company is able to carry out the process of calculating, recording and reporting taxes in terms of PPh 21 income tax in accordance with the current Tax Law and policies.